Dimensi Perutusan dalam Ekaristi Sebagai Persekutuan, Kenangan, dan Perayaan Kehidupan - Lembaga, Evodius Karunia (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2017)
The encyclical letter Ecclesia de Eucharistia of Pope John Paul II,which states that the Church lives from the Eucharist, is the essence of the mystery of the Church. The faithfuls live from the Eucharist where Christ himself is present and sacrifices himself for human beings. Thus, the Eucharist is the heart of the life of the Church. Eucharist as communion signifies that it creates a brotherhood and communion among the faithful, who shall be stated in brotherhood with other fellows outside the Church. The Eucharist as memorial signifies that the memories of the work of God’s redemption in His son, Jesus Christ,are actualized here and now so that the work of salvation presented in the Eucharist should energize the daily life of the faithful. Eucharist as celebration of life indicates that the work of the loving God given to mankind invites people to celebrate it along with others who do not know Christ. The mission dimension of the holy Eucharist means that the work of salvation must be carried out by every Christian throughout the world.